Ketogenic diet - a literature review - Iwona Cuber; Artur Aghadi; Edyta Białowąs; Ewelina Dybała; Magdalena Mazurek; Marta Górna (Journal of Education, Health and Sport, 2023)
Introduction: The ketogenic diet, originally used in the treatment of epilepsy, has recently attracted increasing interest from scientists. There are more and more reports about the possible benefits of using KD.